Media and Face-to-Face Communication Behavior Serang District Communities in Conditions Reducing Cases of Covid-19 - Winangsih, Rahmi; Sagita, Darwis; Mujtaba, Burhanuddin (Indonesian Journal of Social Science Research, 2022)
Media communication behavior is a habit that is carried out by individuals or groups in consuming information through the media.With the Covid-19 case, which was experienced by the entire world's population, it resulted in the emergence of new communication patterns, especially to avoid face-to-face communication processes so as to reduce the spread of the virus that was feared by almost the entire world's population, especially the people in Serang Regency. The purpose of this study was to look at communication behavior and face-to-face communication processes in the condition of the Covid-19 virus in people in Serang Regency. From the results of the research it was revealed that there are people who are still afraid of the virus so that activities in carrying out communication processes such as lectures are carried out online, but there are also people in Serang Regency who are ignorant of health protocols and think that the Covid-19 virus is part of human destiny. must be lived and should not be avoided.